Anti‐irritant and anti‐inflammatory effects of glycerol and xylitol in sodium lauryl sulphate‐induced acute irritation. (14th September 2015) - Szél, E.; Polyánka, H.; Szabó, K.; Hartmann, P.; Degovics, D.; Balázs, B.; Németh, I.B.; Korponyai, C.; Csányi, E.; Kaszaki, J.; Dikstein, S.; Nagy, K.; et al.
Abstract: Background: Glycerol is known to possess anti‐irritant and hydrating properties and previous studies suggested that xylitol may also have similar effects. Objective: Our aim was to study whether different concentrations of these polyols restore skin barrier function and soothe inflammation in sodium lauryl sulphate (SLS)‐induced acute irritation. Methods: The experiments were performed on male SKH‐1 hairless mice. The skin of the dorsal region was exposed to SLS (5%) for 3 h alone or together with 5% or 10% of glycerol respectively. Further two groups received xylitol solutions (8.26% and 16.52% respectively) using the same osmolarities, which were equivalent to those of the glycerol treatments. The control group was treated with purified water. Transepidermal water loss (TEWL) and skin hydration were determined. Microcirculatory parameters of inflammation were observed by means of intravital videomicroscopy (IVM). Furthermore, accumulation of neutrophil granulocytes and lymphocytes, the expression of inflammatory cytokines and SLS penetration were assessed, as well. Results: Treatment with the 10% of glycerol and both concentrations of xylitol inhibited the SLS‐induced elevation of TEWL and moderated the irritant‐induced increase in dermal blood flow and in the number of leucocyte‐endothelial interactions. All concentrations of the applied polyols improved hydration and prevented the accumulation of lymphocytes near the treatment site. At the mRNA level, neither glycerol nor xylitol influenced the expression of interleukin‐1 alpha. However, expression of interleukin‐1 beta was significantly decreased by the 10% glycerol treatment, while expression of tumour necrosis factor‐alpha decreased upon the same treatment, as well as in response to xylitol. Higher polyol treatments decreased the SLS penetration to the deeper layers of the stratum corneum. Conclusion: Both of the analysed polyols exert considerable anti‐irritant and anti‐inflammatory properties, but the effective concentration of xylitol is lower than that of glycerol.